2013
DOI: 10.3390/molecules18089919
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Antiviral Activity of Arrabidaea pulchra (Bignoniaceae)

Abstract: Abstract:The aim of the present work was to carry out a bioguided isolation of antiviral chemical constituents from an ethanol extract of leaves from Arrabidaea pulchra (Cham.) Sandwith (EEAPL) that had shown in vitro activity in a previous screening using DNA and RNA viruses. The activity of EEPAL was evaluated against the DNA viruses Human herpesvirus 1 (HSV-1) and Vaccinia virus Western Reserve (VACV-WR) as well as against the RNA viruses Murine encephalomyocarditis virus (EMCV), and Dengue virus 2 (DENV-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Verbascoside (Figure 1) is obtained from plant species such as, Ansbidaea pulchra , Buddleja brasiliensis , Verbasom phlomoides , Penstemon barbatus and Retzia capensis [220224]. It is recognized for its anti-inflammatory [225], anti-tumor [226], analgesic [227], neuroprotective [228] and antihypertensive [229] properties as demonstrated in several in vitro and in vivo studies.…”
Section: Pkc Modulation By Polyphenolsmentioning
confidence: 99%
“…Verbascoside (Figure 1) is obtained from plant species such as, Ansbidaea pulchra , Buddleja brasiliensis , Verbasom phlomoides , Penstemon barbatus and Retzia capensis [220224]. It is recognized for its anti-inflammatory [225], anti-tumor [226], analgesic [227], neuroprotective [228] and antihypertensive [229] properties as demonstrated in several in vitro and in vivo studies.…”
Section: Pkc Modulation By Polyphenolsmentioning
confidence: 99%
“…Some viral diseases such as dengue or dengue fever (DF), herpes, smallpox, and encephalomyocarditis have a high impact in public health in the tropical and subtropical regions of the world [1]. …”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 390 million cases occur every year around the world and it is endemic in more than 100 countries, including the Americas, Southeast Asia, and Western Pacific, regions most seriously affected [1, 2]. No effective drug as well as no vaccine is available for human use.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds presented have antiviral activity [ 3 ]. A previous work has shown that Bignoniaceae species are promising sources of antiviral compounds [ 5 – 10 ], including phenylethanoids [ 6 , 8 ], which justifies the studies of the antiviral activity in the species of the genus Tecoma , an important group of plants belonging to this botany family. The data obtained in the present study using chromatographic analyzes combined with hyphenated spectrometric techniques showed that the ethanolic extracts of the species under study were rich in phenylethanoids.…”
Section: Introductionmentioning
confidence: 99%